Dual Interfacial Design for Efficient CsPbI2Br Perovskite Solar Cells with Improved Photostability - Tian, Jingjing; Xue, Qifan; Tang, Xiaofeng; Chen, Yuxuan; Li, Ning; Hu, Zhicheng; Shi, Tingting; Wang, Xin; Huang, Fei; Brabec, Christoph J.; Yip, Hin‐Lap; Cao, Yong (Advanced materials (Weinheim), 2019)
A synergic interface design is demonstrated for photostable inorganic mixed‐halide perovskite solar cells (PVSCs) by applying an amino‐functionalized polymer (PN4N) as cathode interlayer and a dopant‐free hole‐transporting polymer poly[5,5′‐bis(2‐butyloctyl)‐(2,2′‐bithiophene)‐4,4′‐dicarboxylate‐alt‐5,5′‐2,2′‐bithiophene] (PDCBT) as anode interlayer. First, the interfacial dipole formed at the cathode interface reduces the workfunction of SnO2, while PDCBT with deeper‐lying highest occupied molecular orbital (HOMO) level provides a better energy‐level matching at the anode, leading to a significant enhancement in open‐circuit voltage (Voc) of the PVSCs. Second, the PN4N layer can also tune the surface wetting property to promote the growth of high‐quality all‐inorganic perovskite films with larger grain size and higher crystallinity. Most importantly, both theoretical and experimental results reveal that PN4N and PDCBT can interact strongly with the perovskite crystal, which effectively passivates the electronic surface trap states and suppresses the photoinduced halide segregation of CsPbI2Br films. Therefore, the optimized CsPbI2Br PVSCs exhibit reduced interfacial recombination with efficiency over 16%, which is one of the highest efficiencies reported for all‐inorganic PVSCs. A high photostability with a less than 10% efficiency drop is demonstrated for the CsPbI2Br PVSCs with dual interfacial modifications under continuous 1 sun equivalent illumination for 400 h. The efficiency and photostability of all‐inorganic mixed‐halide perovskite solar cells (PVSCs) can be simultaneously enhanced by introducing an amino‐functionalized polymer PN4N as a novel cathode interlayer and dopant‐free PDCBT hole‐transporting layer. The favorable interaction between perovskite crystal and PN4N/PDCBT can effectively improve CsPbI2Br film quality, with power conversion efficiency over 16%.